Pelatihan Buketpreneurship Guna Membangun Keterampilan Entrepreneur Menuju Wirausaha Unggul - Islami, Intan Bungo; Rahma, Laila; Rizqiyah, Rofiatur; Dzilkamil, Khabibah; Adinugraha, Hendri Hermawan (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2024)
In accordance with the theme of this training, namely